Phytochemical analysis and evaluation of the antibacterial and antibiotic potentiation activities of the aqueous extract of Cordia oncocalyx Allemão (Boraginaceae) - José Thyalisson da Costa Silva; José Jailson Lima Bezerra; Talysson Felismino Moura; Rafael Pereira da Cruz; Maraiza Gregorio de Oliveira; Adrielle Rodrigues Costa; Felicidade Caroline Rodrigues; João Arthur de Oliveira Borges; Terezinha Raila Ramos de Sousa; Maria Flaviana Bezerra Morais-Braga; Henrique Douglas Melo Coutinho; José Weverton Almeida-Bezerra (Pharmaceutical Science Advances)
The global antibiotic resistance crisis highlights the inappropriate use of medicines by the population and the lack of development of new antimicrobial agents. According to various studies, natural products are promising alternatives for combating bacterial resistance and treating infectious diseases. Accordingly, the present study aimed to analyze the chemical composition and evaluate the antibacterial and antibiotic potential of an aqueous extract of Cordia oncocalyx Allemão (AECO). Phytochemical analyses were performed using high-performance liquid chromatography equipped with a diode array detector (HPLC-DAD). The minimum inhibitory concentration (MIC) was used to evaluate the antibacterial activity of C. oncocalyx against conventional and multidrug-resistant (MDR) bacterial strains (Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus). According to HPLC-DAD analysis, the following compounds could be identified in the aqueous extract of C. oncocalyx: luteolin (3.07 ± 0.04 mg/g), caffeic acid (1.05 ± 0.03 mg/g), ellagic acid (0.62 ± 0.05 mg/g), and quercetin (0.58 ± 0.01). AECO did not exhibit antibacterial activity when administered alone (MIC >512 μg/mL). However, when combined with gentamicin, ampicillin, and norfloxacin, AECO potentiated the action of these antibiotics against the multi-resistant strains of P. aeruginosa and S. aureus. Although clinical relevance was not revealed by the in vitro tests against pathogenic bacteria, AECO can combined with commercial antibiotics to improve their antibacterial effects. Future studies focusing on the mechanisms of action of the compounds isolated from C. oncocalyx and toxicological tests are fundamental.